Variation In Seed Quality Of Radish Preserved In Different Storage Containers (Bangladesh Journal of Agricultural Research, 2013)
Abstract not available DOI: http://dx.doi.org/10.3329/bjar.v38i3.16981 Bangladesh J. Agril. Res. 38(3): 545-552, September 2013